The Effectiveness of the Implementation of Practicum on Office Technology Learning - Nasrullah, Muh.; Nurjihan, Naurah; Nasir, Nasir; Tamam, Moh. Badrut (International Journal of Administration and Education (IJAE), 2025)
The rapid development of technology requires vocational schools to produce graduates with strong office technology competencies. This study aims to determine the effectiveness of practicum implementation in Office Technology learning for grade XI students of MPLB 1 SMK Negeri 1 Gowa. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. The analysis focused on five indicators: improving understanding, creating deeper impacts, better knowledge retention, breaking the monotony of memorization, and increasing confidence. The results reveal that practicum activities effectively improve students’ understanding of office technology concepts, strengthen their ability to apply knowledge in real contexts, and enhance confidence in performing administrative tasks. Students were also found to retain knowledge longer when learning through hands-on experience compared to theoretical instruction alone. These findings align with Kolb’s experiential learning theory, emphasizing that learning occurs through direct experience and reflection. The study highlights that limited laboratory facilities remain a challenge but can be addressed through creative scheduling and peer collaboration. The novelty of this research lies in its focus on evaluating practicum effectiveness from students’ direct learning experiences rather than conventional learning outcomes. The findings reinforce the importance of integrating practice-based approaches into the vocational curriculum to improve office technology competencies and workplace readiness.